PENGARUH PENGENDALIAN INTERNAL, GOOD GOVERNANCE, PERANAN AUDITOR INTERNAL, DAN KEADILAN ORGANISASI TERHADAP TINGKAT KECURANGAN (Studi Pada SKPD Kabupaten Rokan Hulu) - Syarif, Muqti Randy; ', Kirmizi; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study is to find out the effect of the internal control, good governance, the role of the internal auditor, and organization justice on the level of fraud. The population of this study were civil servants whose working in government agencies (29 agencies) in Rokan Hulu regency. This research is using purposive sampling method. Data that used in this research is primary data by deliverying the quesioners directly to the government agencies in Rokan Hulu. Total respondents which is used in this research are 76 respondents (87.35 %). The analyzing method is Double Regression methods using SPSS (Statistical Product and Service Solution) version 20. The t test, F test, and determination coefisien test was used to test the hypothesis. Result of the study indicates that internal control, good governance, the role of the internal auditor, and organization give negative influence on the level of fraud. All of the independent variables jointly influence dependent variables as much as 70.9%, while 29.1% is influenced by other unclear variable.Keywords : Control, Governance, Auditor, Justice, and Fraud.